APPLICATION OF SELF-TALK TECHNIQUE TO OVERCOME INTERPERSONAL COMMUNICATION BARRIERS OF BLIND CLIENT H - Rahayu, Intan; Noviza, Neni; Marianti, Lena (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to determine the application of self-talk techniques in overcoming barriers to interpersonal communication in client "H". Interpersonal communication is a direct interaction between two or more people in which a message can be conveyed and responded to directly. Interpersonal communication barriers occur when communication between two or more people does not go smoothly. This is caused by factors that interfere with one of the stages in the communication process, so that the communication that takes place becomes ineffective. The approach used in this study is a qualitative approach using the case study research method. The data collection techniques used in this study are observation, interview, and documentation methods. Meanwhile, the data analysis technique used in this study is the data analysis method of Robert K Yin's case study. The results of this study show that the cause of client "H" having interpersonal communication barriers is that client "H" has limitations in self-expression, uncertainty in message delivery, discomfort in communication, and anxiety about the judgment of others. After applying the self-talk technique, there was a significant change in client "H", namely, where client "H" became more confident in expressing his opinion, more able to express his feelings clearly, and more open in establishing relationships with others. Based on the results of the application of the self-talk technique to overcome the interpersonal communication barriers of client "H", it can be concluded that this technique is effective or successful in overcoming the barriers to interpersonal communication.